Enhanced infection and transmission of the 2022–2024 Oropouche virus strain in the North American biting midge Culicoides sonorensis - Stacey L.P. Scroggs; Jessica Gutierrez; Lindsey M. Reister-Hendricks; Krista B. Gunter; Natasha L. Tilston; Bethany L. McGregor (Scientific Reports)
Abstract Oropouche virus (OROV) is a vector-borne zoonotic virus that causes febrile illness in humans. Biting midges of the Culicoides genus are the primary vectors during human outbreaks. The 2022–2024 OROV outbreak has seen an increase in incidence, geographic expansion, and the emergence of previously undocumented symptoms. To better understand the basis of increased disease incidence, infection of the outbreak virus (OROV240023) was compared to a historical virus strain (rOROVBeAn19991) in Culicoides sonorensis, a midge species that has demonstrated historical competence. Higher levels of infection, dissemination, and transmission potential were observed in C. sonorensis infected with the outbreak strain compared to the historical strain, although infectious titers did not differ between the two viruses. OROV240023 was also detected in saliva at earlier time points than rOROVBeAn19991, indicating a shorter extrinsic incubation period of < 5 days compared to 7–14 days for rOROVBeAn19991. Taken together, our results demonstrate increased transmission potential of the outbreak strain in C. sonorensis midges, raising concern about the risk of spread within the United States following potential introduction. However, further studies are needed to evaluate the current strain in Culicoides species occurring within its outbreak range, including Culicoides paraensis, the confirmed South American vector of OROV.